Revolutionary path - Nkruman, Kwame (New York : International Publishers, 1973)
The struggle for national liberation, 9. -- Socialist construction and the struggle for thr liberation and unification of Africa 1957-1966, 125. -- Class struggle, and the armed phase of the african revolution, 389